2011
DOI: 10.1103/physrevlett.107.014501
|View full text |Cite
|
Sign up to set email alerts
|

Collective Beating of Artificial Microcilia

Abstract: We combine technical, experimental, and theoretical efforts to investigate the collective dynamics of artificial microcilia in a viscous fluid. We take advantage of soft lithography and colloidal self-assembly to devise microcarpets made of hundreds of slender magnetic rods. This novel experimental setup is used to investigate the dynamics of extended cilia arrays driven by a precessing magnetic field. Whereas the dynamics of an isolated cilium is a rigid body rotation, collective beating results in a symmetry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 16 publications
1
54
0
Order By: Relevance
“…[ 37,39 ] Magnetic cilia dynamics in a precessing field have interesting features when the collective effects due to the hydrodynamic interactions in the carpet are important. [ 40 ] In this case, the trajectory of the tip of a single cilia in the rectangular carpet transforms from a circle to a ellipse as the frequency of the precessing field increases. [ 40 ] Hydrodynamic flow induced by precessing cilia was studied in ref.…”
Section: Ciliamentioning
confidence: 97%
See 1 more Smart Citation
“…[ 37,39 ] Magnetic cilia dynamics in a precessing field have interesting features when the collective effects due to the hydrodynamic interactions in the carpet are important. [ 40 ] In this case, the trajectory of the tip of a single cilia in the rectangular carpet transforms from a circle to a ellipse as the frequency of the precessing field increases. [ 40 ] Hydrodynamic flow induced by precessing cilia was studied in ref.…”
Section: Ciliamentioning
confidence: 97%
“…[ 40 ] In this case, the trajectory of the tip of a single cilia in the rectangular carpet transforms from a circle to a ellipse as the frequency of the precessing field increases. [ 40 ] Hydrodynamic flow induced by precessing cilia was studied in ref. [ 38 ] .…”
Section: Ciliamentioning
confidence: 97%
“…This is quite different from the rotatable rod additive and the rotatable, stretchable, and breakable polymer additives, used for hydrodynamic turbulence reduction [4][5][6]. The previous studies showed that rotating the magnetized chain by an external rotating B field can excite vortices and enhance chaotic mixing of the background liquid [36][37][38]. Inversely, in our system, the chain alignment by the static B field can retard the flow transverse to the chain, especially the vortices with vorticity transverse to the chain.…”
Section: Resultsmentioning
confidence: 78%
“…In the biological world, surface flows are often created along tissues, or groups of cells, by the time-varying beating of short cilia [7] resulting in effective slip boundary conditions for the neighbouring flow [8,9]. Although artificial cilia have been realised in the lab, the dynamics and performance of biological ciliary arrays has proven difficult to reproduce experimentally [10][11][12], Instead, a popular method to generate flows near surfaces in the lab consists in taking advantage of phoretic mechanisms where externally-applied physico-chemical gradients (such as charge, temperature, composition...) create local body forces on the fluid in thin layers near surfaces which, through the action of viscous stresses, entrain a bulk flow [13]. A famous example of such methods is electrophoresis wherein an electric field applied along a channel filled with an electrolyte drives a flow due to charge imbalance near the electrical double layer at the junction between the fluid and surfaces [5].…”
Section: Introductionmentioning
confidence: 99%